2013
DOI: 10.1128/jcm.02036-13
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of a Commercial Cytomegalovirus Quantitative Standard: Effects of Commutability on Interlaboratory Concordance

Abstract: Commutability of quantitative reference materials has proven important for reliable and accurate results in clinical chemistry. As international reference standards and commercially produced calibration material have become available to address the variability of viral load assays, the degree to which such materials are commutable and the effect of commutability on assay concordance have been questioned. To investigate this, 60 archived clinical plasma samples, which previously tested positive for cytomegalovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 14 publications
0
20
1
Order By: Relevance
“…This has primarily been demonstrated on a smaller scale, with just a few assays. In the latter case, implementation of common, commercially produced standards could only improve agreement among labs when commutable and actually could reduce agreement when noncommutable (17). Other factors may come into play as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has primarily been demonstrated on a smaller scale, with just a few assays. In the latter case, implementation of common, commercially produced standards could only improve agreement among labs when commutable and actually could reduce agreement when noncommutable (17). Other factors may come into play as well.…”
Section: Discussionmentioning
confidence: 99%
“…Commutability of reference material is critical to producing quantitative values reflective of reality in vivo and is a necessary ingredient if such material is to reduce variability among laboratories. In fact, commutable quantitative standards have been shown to improve interlaboratory agreement, while noncommutable standards have actually been shown to increase disparity among testing centers (17). Here we examine the commutability of the first WHO International Standard (WHO IS) for HCMV (09/162), among a wide variety of commonly used CMV quantitative assays.…”
mentioning
confidence: 99%
“…The use of common secondary standards in some cases has been shown to increase agreement among laboratories using various quantitative assays (6,14,20). However, noncommutable standards may actually decrease interlaboratory/interassay agreement (22). It is clear that in some cases, some secondary standards showed similar results across different assays, and some showed improved agreement compared with the digital results rather than with the nominal values of secondary standards.…”
Section: Tablementioning
confidence: 83%
“…Finally, the percentages of specimens that fell within various ranges were plotted (e.g., 15% of the samples were within 0.1 log 10 and 100% of the samples were within 1.0 log 10 ), as previously described (Fig. 2C) (12). This analysis revealed that the quantitative agreement between assays was unchanged when calibrated to the WHO standard.…”
Section: Iral Load Testing For Epstein-barr Virus (Ebv) Is Importantmentioning
confidence: 99%
“…Commutability refers to the ability of a reference material to have interassay properties comparable to the properties demonstrated by authentic clinical samples (9). Critically, the use of reference materials that lack commutability may reduce quantitative agreement (10)(11)(12). We therefore evaluated the commutability of the EBV WHO standard across two common real-time PCR assays, the laboratory-developed BamHI and the commercial artus EBV QIAsymphony Rotor-Gene Q (QS-RGQ) assays.…”
Section: Iral Load Testing For Epstein-barr Virus (Ebv) Is Importantmentioning
confidence: 99%